Visible Expression of Social Identity: the Clothing and Fashion - Nihan AKDEMİR (Gaziantep Üniversitesi Sosyal Bilimler Dergisi, 2018)
This paper includes the investigation about the relation between social identity and clothing and also fashion. And this relationship has been taken into consideration over the visual expression because even during the ancient times, the cloths were the basic and simple way of representing the identity and social classes. The visible expression of identity over clothing from Ancient Egypt to today’s clothing and fashion has been researched in this article. And the results have showed that every pieces of clothing from fabric to colouring have visual significations about social identity.